Ubiquity of polystyrene digestion and biodegradation within yellow mealworms, larvae of Tenebrio molitor Linnaeus (Coleoptera: Tenebrionidae). (December 2018) - Yang, Shan-Shan; Wu, Wei-Min; Brandon, Anja M.; Fan, Han-Qing; Receveur, Joseph P.; Li, Yiran; Wang, Zhi-Yue; Fan, Rui; McClellan, Rebecca L.; Gao, Shu-Hong; Ning, Daliang; Phillips, Debra H.; et al.
Abstract: Academics researchers and "citizen scientists" from 22 countries confirmed that yellow mealworms, the larvae of Tenebrio molitor Linnaeus, can survive by eating polystyrene (PS) foam. More detailed assessments of this capability for mealworms were carried out by12 sources: five from the USA, six from China, and one from Northern Ireland. All of these mealworms digested PS foam. PS mass decreased and depolymerization was observed, with appearance of lower molecular weight residuals and functional groups indicative of oxidative transformations in extracts from the frass (insect excrement). An addition of gentamycin (30 mg g −1 ), a bactericidal antibiotic, inhibited depolymerization, implicating the gut microbiome in the biodegradation process. Microbial community analyses demonstrated significant taxonomic shifts for mealworms fed diets of PS plus bran and PS alone. The results indicate that mealworms from diverse locations eat and metabolize PS and support the hypothesis that this capacity is independent of the geographic origin of the mealworms, and is likely ubiquitous to members of this species. Graphical abstract: Highlights: Consumption of polystyrene (PS) by mealworms observed in 22 countries. PS degrades in mealworms obtained from 12 locations in the USA, UK and China. Addition of nutrition enhances survival rate and PS consumption rate. Antibiotics depresses gut microbes and severely inhibits PS degradation. PS feeding shifts mealworm gut microbiome.